Transforming Digital Teaching Practices: The Role of Empowering Leadership and Self-Efficacy in Emancipated Schools - Syunu Trihantoyo; Mufarrihul Hazin; Windasari Windasari; Shelly Andari; Rezki Nurma Fitria; Muhammad Faizal A Ghani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Despite the increasing relevance of digital competence in education, elementary school teachers' digital learning behaviors often do not align with current expectations. Enhancing these behaviors is essential for building an inclusive school ecosystem. This study investigates the impact of principals' empowering leadership on teachers' digital learning behavior, with self-efficacy as a mediating factor.A quantitative research design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through purposive sampling from 340 teachers participating in the emancipated school program. Respondents were selected based on their involvement in schools with digitally transformative leadership and self-efficacy development initiatives. The analysis followed three stages: (1) validity and reliability testing; (2) model fit assessment; and (3) hypothesis testing.The findings revealed that empowering leadership directly influences digital learning behavior, accounting for 65.4% of the variance. Additionally, self-efficacy plays a mediating role, contributing 29.5%. Although empowering leadership emerged as the dominant factor, the mediation effect suggests that self-efficacy remains a crucial element in fostering effective digital learning behaviors among teachers. The study highlights that teachers with higher self-efficacy are more receptive to empowering leadership, especially in the context of digital learning. These findings underscore the importance of fostering both strong leadership and personal belief in capability to promote sustainable digital competence in schools.